Celastrol Attenuates Angiotensin II–Induced Cardiac Remodeling by Targeting STAT3. Issue 8 (10th April 2020) - Ye, Shiju; Luo, Wu; Khan, Zia A.; Wu, Gaojun; Xuan, Lina; Shan, Peiren; Lin, Ke; Chen, Taiwei; Wang, Jingying; Hu, Xiang; Wang, Shengjie; Huang, Weijian; et al.
Abstract : Rationale: Excessive Ang II (angiotensin II) levels lead to a profibrotic and hypertrophic milieu that produces deleterious remodeling and dysfunction in hypertension-associated heart failure. Agents that disrupt Ang II–induced cardiac dysfunction may have clinical utility in the treatment of hypertension-associated heart failure. Objective: We have examined the potential effect of celastrol—a bioactive compound derived from the Celastraceae family—on Ang II–induced cardiac dysfunction. Methods and Results: In rat primary cardiomyocytes and H9C2 (rat cardiomyocyte-like H9C2) cells, celastrol attenuates Ang II–induced cellular hypertrophy and fibrotic responses. Proteome microarrays, surface plasmon resonance, competitive binding assays, and molecular simulation were used to identify the molecular target of celastrol. Our data showed that celastrol directly binds to and inhibits STAT (signal transducer and activator of transcription)-3 phosphorylation and nuclear translocation. Functional tests demonstrated that the protection of celastrol is afforded through targeting STAT3. Overexpression of STAT3 dampens the effect of celastrol by partially rescuing STAT3 activity. Finally, we investigated the in vivo effect of celastrol treatment in mice challenged with Ang II and in the transverse aortic constriction model. We show that celastrol administration protected heart function in Ang II–challenged and transverse aortic constriction–challenged mice by inhibiting cardiac fibrosis and hypertrophy. Conclusions: Our studies show that celastrol inhibits Ang II–induced cardiac dysfunction by inhibiting STAT3 activity. Abstract : Supplemental Digital Content is available in the text.